Produção de farinha de grão de bico (Cicer arientinum L.) e aplicação na formulação de biscoito tipo cookie vegano - Kanai, Rafaela Soares dos Santos (2021)
Vegan and vegetarian consumers represent an attractive economic slice for the food industry, since the dietary need for protein of this public is usually supplied by the ingestion of legumes and their derivatives, motivating the development of new products for this segment. In this context, chickpea flour stands out as a potential ingredient in the formulation of vegan cookies. The cookies are products of easy production and access to the population, being commercialized in several ways and consumed by individuals of various age groups. The objective of this work was to produce chickpea flours with different process characteristics and apply them in the formulation of vegan cookies. Two flours, named heavy chickpea flour (FGBP) and light chickpea flour (FGBL) were developed and their physicochemical and technological characteristics were compared to a commercial chickpea flour (FGBC). Then, all flours were used in the production of vegan cookies and proximate composition, physical and microbiological characterization, and sensorial acceptance test were performed. In general, the produced flours presented higher concentration of protein and dietary fiber than the commercial flour and the three flours presented significant difference in color. In relation to the technological properties, the FGBP obtained the highest value of water absorption capacity and there was no difference among the samples in oil absorption capacity. In relation to the cookies developed, there was no difference in their proximal composition and due to the protein concentration (14.42 to 15.11%), they can be considered as food with high protein content according to the Brazilian legislation. The microbiological results of all cookies were satisfactory, respecting the allowed by the legislation, characterizing the product as safe for consumption. Although the cookies had differences in instrumental color and texture, this was not detected by the testers in the sensory analysis, because the mean scores of the attributes (appearance, texture, aroma, flavor and overall acceptance) evaluated were statistically equal. Besides, all the attributes of the sensory evaluation varied from "I liked moderately" to "I liked very much". Thus, it can be concluded that chickpea flour is a promising ingredient for cookie formulation, being a viable vegan option for those seeking a product with high nutritional value.